2012
DOI: 10.3892/or.2012.2003
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 overexpression in human non-small cell lung cancer correlates with cell migration and invasion through the activation of the Notch1 signaling pathway

Abstract: A disintegrin and metalloproteinase 10 (ADAM10) was identified as a key protease in the ectodomain shedding of various substrates, such as Notch1 protein, ErbB2 and E-cadherin, which are important in the development of non-small cell lung cancer (NSCLC). The aim of this study was to investi-gate the role of ADAM10 in NSCLC metastasis.We characterized the expression of ADAM10 and Notch1 in human NSCLC tissues in vivo. Immunohistochemical analysis indicated that ADAM10 expression was significantly increased in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 40 publications
4
56
0
Order By: Relevance
“…Expression levels of several components of the Notch pathway, which can be cleaved by ADAM10, were upregulated in melanomas compared with common melanocytic nevi (35). Guo et al (15) presented further evidence that ADAM10 promotes non-small cell lung cancer (NSCLC) cell migration and invasion via the activation of the Notch1 signaling pathway. In another study, Gutwein et al (36) demonstrated that the release of cell-associated adhesion molecules such as L1 may be relevant to promote cell migration, and L1 release in AR breast carcinoma cells is mediated by ADAM10.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Expression levels of several components of the Notch pathway, which can be cleaved by ADAM10, were upregulated in melanomas compared with common melanocytic nevi (35). Guo et al (15) presented further evidence that ADAM10 promotes non-small cell lung cancer (NSCLC) cell migration and invasion via the activation of the Notch1 signaling pathway. In another study, Gutwein et al (36) demonstrated that the release of cell-associated adhesion molecules such as L1 may be relevant to promote cell migration, and L1 release in AR breast carcinoma cells is mediated by ADAM10.…”
Section: Discussionmentioning
confidence: 96%
“…To date, 13 catalytically active ADAMs have been identified in the human genome (11,12). One member of the ADAM family, A disintegrin and metalloproteinase 10 (ADAM10), has recently been reported to play important roles in cell migration, tumor development and metastasis by proteolytic shedding of cell surface proteins and has been demonstrated to be a positive regulator of cancer progression in renal cell carcinoma (13), pancreatic carcinoma (14), lung cancer (15), gastric carcinoma (16), oral squamous cell carcinoma (17) and melanoma (18). Proteolytically active ADAM10 acts as an ectodomain sheddase, which releases extracellular regions of membrane-bound proteins (e.g., adhesion molecules, growth factors, cytokines, chemokines and receptors).…”
Section: Introductionmentioning
confidence: 99%
“…To down-regulate β-catenin or Axin in tumor cells, the cells were transfected with control or target shRNA, which were respectively cloned into shRNA expression vector, pGenesil-4, with U6 promoter (Genesil Corp., Wuhan, China), containing selectable marker GFP to facilitate the selection of stably transfected cells as described previously (Guo et al, 2012). After screened with G418, the cells were used for further experiments.…”
Section: Cell Shrna Transfectionmentioning
confidence: 99%
“…A number of ADAMs, including ADAM9, ADAM10, ADAM12 and ADAM17, are critical during the genesis, development and metastasis of cancers (21,25,26). Dysregulated expression of ADAM10 has been reported in various malignancies, and has been suggested to be involved in cancer progression (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ADAM family members, including ADAM10, serve pivotal roles in the pathogenesis or progression of cancers, including proliferation, angiogenesis, migration and invasion (6)(7)(8)(9). Analysis of gene expression profiles revealed that the ADAM10 gene was significantly overexpressed in a wide variety of human malignancies, including hepatocellular carcinoma, melanoma, oral squamous cell carcinoma, lung cancer, pancreatic carcinoma, and gastric and bladder cancer (10)(11)(12)(13)(14)(15)(16)(17). Accumulating evidence has illustrated that ADAM10 contributed to the regulation of cancer progression, chemoresistance and metastasis via the cleavage of growth factors or cell surface proteins (6,8,10,12,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%